2010
DOI: 10.1093/jb/mvq023
|View full text |Cite
|
Sign up to set email alerts
|

Control of signalling properties of human somatostatin receptor subtype-5 by additional signal sequences on its amino-terminus in yeast

Abstract: The yeast Saccharomyces cerevisiae is known as an available host for human G-protein-coupled receptor (GPCR) ligand screening. Although several types of yeast signal sequences (SS) attached with the GPCRs could improve their productivities and facilitate transportation of the GPCRs to the yeast plasma membrane, the effects of additional SS on ligand-specific signalling functions of GPCRs are not reported. Here, we demonstrated the controlling signalling properties by addition of SS using engineered yeast as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…Although some of ODR-10 was localised to the yeast plasma membrane, much of it was localised intracellularly (Figure 1), which has also previously been observed for mammalian chemoreceptors [34], [43], [44]. However, it has also been shown that mammalian olfactory receptors are functional whether they are localised to yeast ER, Golgi or plasma membrane when tested in vitro [34], [43], [44]. Based on these previous reports, we believe it is reasonable to infer that ODR-10 is correctly folded whether it is located in the plasma or intracellular membranes [35].…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Although some of ODR-10 was localised to the yeast plasma membrane, much of it was localised intracellularly (Figure 1), which has also previously been observed for mammalian chemoreceptors [34], [43], [44]. However, it has also been shown that mammalian olfactory receptors are functional whether they are localised to yeast ER, Golgi or plasma membrane when tested in vitro [34], [43], [44]. Based on these previous reports, we believe it is reasonable to infer that ODR-10 is correctly folded whether it is located in the plasma or intracellular membranes [35].…”
Section: Resultssupporting
confidence: 76%
“…In yeast cells co-expressing ODR-10-GFP 2 and ODR-10-Rluc, ODR-10-GFP 2 was localised to the plasma membrane in ≈32% of cells after a 4 hour induction (Figure 1). Although some of ODR-10 was localised to the yeast plasma membrane, much of it was localised intracellularly (Figure 1), which has also previously been observed for mammalian chemoreceptors [34], [43], [44]. However, it has also been shown that mammalian olfactory receptors are functional whether they are localised to yeast ER, Golgi or plasma membrane when tested in vitro [34], [43], [44].…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…We constructed several negative controls by eliminating the S-14 peptide or by replacing it with agonistic peptides for other GPCRs (Figure 2B and Table 1). We expressed hemagglutinin (HA)-tagged human SSTR5 on the yeast cell surface using previously reported plasmids [5], [6] (Table 1). We used these expression and mock plasmids to investigate the ability of the S-14–Flag–Flo42 autocrine peptide to activate GPCR signaling (Figure 4).…”
Section: Resultsmentioning
confidence: 99%